Acoustic performance of sonic metacage consisting of Helmholtz's resonator columns with internal partitions. (July 2022) - Kumar, Sanjay; Lee, Heow Pueh
Highlights: Demonstrated a 3D acoustic metacage for hybrid noise shielding and ventilation purposes. The metacage is assembled using cylindrical columns and two different design types (C2 and K2). Each column comprises two half-cylindrical Helmholtz resonator cavities with opening slots. The structure is designed for noise attenuation at a target frequency of 2500 Hz. Sound insertion loss value of 20.8 dBA is achieved for K2 type metacage when a noise source is outside. Abstract: The quest for a quiet environment has led to numerous efforts to shield noise at the source or develop an efficient acoustic proof system. We present a three-dimensional sonic crystal acoustic metacage structure for hybrid purposes of noise shielding and natural ventilation. The metacage prototype comprises sixteen cylindrical sonic crystal column structures (C2 and K2 types) placed at a regular distance along the circular periphery. Each column consists of two semi-cylindrical long cavities with slit channels, which allow the sound wave to enter the Helmholtz cavities and are responsible for sound attenuation. Numerical simulations and experimental measurements are used to demonstrate the efficacy of the acoustic metacage. Experimental measurements display the maximum sound insertion loss values of 20.8 dBA and 11.9 dBA for K2 type sonic crystal metacage, respectively, when the sound source is placed outside and inside the cage. For C2 type sonic crystal metacage, two sound insertion loss peaks with maximum values of 19.8 dBA and 10.4 dBA have been achieved at 2500 Hz when the sound source is kept outside and inside. The numerical results suggest the frequency tuning capabilities by adjusting the metacage size. Also, the modular design features enable the tunable operating frequency to meet different requirements.